The Incentives for Takeover in Oligopoly - Roman Inderst; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
We present a model of takeover where the target optimally sets its reserve price. Under relatively standard symmetry restrictions, we obtain a unique equilibrium. The probability of takeover is only a function of the number of firms and of the insiders' share of total industry gains due to the increase in concentration. Our main application is to the linear Cournot and Bertrand models. A takeover is more likely under Bertrand competition if goods are substitutes and more likely under Cournot competition if goods are complements.
Keywords: L13; D43; L41; 330; Takeover bidding; Merger incentives; Oligopoly; Übernahme; Fusion; Oligopol; Duopol; Ökonomischer Anreiz; Theorie